The Governance of Digital Transformation in ‎Educational Districts in the Kingdom of Saudi ‎Arabia - Al-Mufeez, Khawlah; Al-Otaibi, Samiah (Jordan Journal of Educational Sciences, 2023)
This study aimed to identify the degree of the implementation of digital transformation governance in educational administrations in the Kingdom of Saudi Arabia and its requirements. To achieve the objectives of this study, a descriptive survey approach was used and the instrument used was the questionnaire. The study community consisted of information technology administration employees. This study reported a number of results, the most important of which are as follows: All dimensions of the degree of the implementation of the digital transformation governance in the educational administrations in the Kingdom of Saudi Arabia were highly practiced. The dimension of techniques and technologies of operational processes came first, succeeded by the dimension of authorities and administration and the dimension of resources and services third, and finally the dimension of accountability was fourth